FILTRAÃ‡ÃƒO E SIFONAMENTO NO PRÃ‰-TRATAMENTO DE AMOSTRAS DE TERRA PARA ANÃLISE MECÃ‚NICA - Fujihira, Kanae; Freire, Octavio; Ranzani, Guido (REVISTA DE AGRICULTURA, 2020)
FILTRAÃ‡ÃƒO E SIFONAMENTO NO PRÃ‰-TRATAMENTO DE AMOSTRAS DE TERRA PARA ANÃLISE MECÃ‚NICA